Receiver DCB Estimation and Analysis by Types of GPS Receiver - Byung-Kyu Choi; Jong-Kyun Chung; Jeong-Ho Cho (Journal of Astronomy and Space Sciences, 2010)
This paper analyzes that the global positioning system (GPS) receiver differential code bias (DCB) has effect on the estimation the ionosphere total electron content (TEC). The data from nine permanent GPS sites of the Korea Astronomy and Space Science Institute (KASI) were used for the estimation of the receiver DCB before (Trimble 4000 SSi) and after (Trimble NetRS) the receiver replacement, using the singular value decomposition method. The results showed that the estimated mean value of the receiver DCB varied from 0.11 ns (nanosecond) to 7.54 ns before the receiver replacement, but the receiver DCBs shoed large values than 20 ns except some stations after the replacement. The receiver DCB showed a relatively large difference by types of the receivers, and, as a result, it had a great effect on the estimation the ionosphere TEC using GPS.